When Foul Play Seems Fair: Dishonesty as a Response to Violations of Just Deserts - Reuben Kline; Fabio Galeotti; Raimondello Orsini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2014)
We investigate the norm of just deserts and its effect on honesty. Just deserts is an essential norm in a market society, and honesty is an important factor in economic and social exchange. In particular, we analyze what happens when the social distributive rules betray the reasonable expectation that who deserves more will obtain a larger payoff. Using a formal-theoretic framework—equity theory—we explore the nexus between the perception of just deserts and honesty, combining cross-national survey (WVS) evidence and data from two laboratory experiments—conducted in the United States and Italy—to study whether violations of the principle of just deserts contribute to an increased tolerance for or an engagement in dishonest and corrupt acts. We find convergent evidence that violation of the just deserts norm results in a greater propensity toward self-serving dishonesty, and that this effect is distinct from the effect of inequality. Both the survey and experimental results also indicate that sensitivity to violations of the just deserts norm vary cross-nationally. We conclude with a discussion of the implications of our results for theories of distributive justice and multiple equilibria in societal levels of honesty.
Keywords: C91; D03; D31; D63; H26; 330